Peningkatan Kreativitas Belajar Siswa melalui Media Pembelajaran Digital Interaktif di UPT SPF SD Inpres Antang 1 Kota Makassar - Wahid, Abdul; Afni, Nur; Hastati, Sri; Nurdiansyah, Erwin; Kaddas, Badruddin; Rahmawati, Rahmawati (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This activity aims to enhance student learning creativity through the use of interactive digital learning media at the SPF (School Education Unit) of SD Inpres Antang 1, Makassar City. Based on initial observations and discussions with local teachers, it was found that most learning processes were still conventional and lacked technological involvement. Therefore, the community service team designed and implemented training and mentoring for elementary school teachers on the use of interactive digital learning media, such as Canva for Education, Wordwall, and Liveworksheets, which can be used in thematic learning. The implementation method for this activity included socialization, training, hands-on practice, and evaluation. Fifteen teachers from various grade levels at the school participated in the activity. The results showed that the teachers were able to independently develop and use interactive digital learning media and began implementing them in their teaching and learning activities. Consequently, based on teacher reflections and classroom observations, students became more active and enthusiastic, and showed improvements in their ability to express ideas and complete creative assignments.